Implications of unprofitable horizontal mergers : a re-interpretation of the Farrell-shapiro-Framework - Oliver Budzinski; Jürgen-Peter Kretschmer (Philipps-Universität Marburg, Fachbereich Wirtschaftswissenschaften, 2007)
We demonstrate that the popular Farrell-Shapiro-framework (FSF) for the analysis of mergers in oligopolies relies regarding its policy conclusions sensitively on the assumption that rational agents will only propose privately profitable mergers. If this assumption held, a positive external effect of a proposed merger would represent a sufficient condition to allow the merger. However, the empirical picture on mergers and acquisitions reveals a significant share of unprofitable mergers and economic theory, moreover, demonstrates that privately unprofitable mergers can be the result of rational action. Therefore, we extend the FSF by explicitly allowing for unprofitable mergers to occur with some frequency. This exerts a considerable impact on merger policy conclusions: while several insights of the original FSF are corroborated (f.i. efficiency defence), a positive external effect does not represent a sufficient condition for the allowance of a merger anymore. Applying such a rule would cause a considerable amount of false positives. In addition, we conclude that the FSF need to be explicitly complemented by a freedom of competition principle in order to make it workable as a basis for an economics-based merger policy.
Keywords: L13; L41; K21; D43; 330; oligopoly theory; horizontal merger policy; profitability of mergers; freedom of competition; antitrust